Critical Factors to Green Marketing Strategies Implementation of Chinese Enterprises - Shi, Yunluo; Yang, Yang (Journal of Marketing Development and Competitiveness, 2018)
Combining with 4P theory, organization theory, environment theory, this paper mainly focuses on the contributory factors of implementing green marketing strategies for enterprises. Through applying DEMATEL method, the research deeply analyzes the mutual influence relationships of the criteria, draws the Influential Network Relation Map, and gives the weight of each dimension based on ANP method. The results show that among the three evaluation dimensions, 4P possesses the largest influence degree, followed by organization dimension and environment dimension, indicating that the general influence degree of 4P dimension is the largest in the overall structure, making it the most important influence dimension.